التفكير الإيجابي لدى الطلبة الجامعيين دراسة ميدانية بالأغواط - علة, عيشة; بوزاد, نعيمة (جامعة الوادي University of Eloued, 2016)
هدفت الدراسة الحالية البحث في التفكير الإيجابي لدى الطلبة الجامعيين بجامعة ثليجي عمار بالأغواط ومن خلال التساؤلات التالية: ماهو مستوى التفكير الإيجابي لدى الطلبة الجامعيين؟ ماهي الأبعاد الأكثر شيوعا بين الطلبة الجامعيين؟ هل توجد فروق ذات دلالة إحصائية في أبعاد التفكير الإيجابي وفقا للنوع؟، وللإجابة عن هذه التساؤلات استخدمنا مقياس التفكير الإيجابي لعبد الستار(2010) على عينة من الطلبة حيث بلغ عددهم 200 طالبا حيث توصلنا مجموعة من النتائج أهمها: ارتفاع مستوى التفكير الإيجابي لدى الطلبة الجامعيين، أما الأبعاد الأكثر شيوعا فقد جاء الشعور العام بالرضا أولا، ثم التقبل الإيجابي للاختلاف، حب التعلم والتفتح المعرفي الصحي، السماحة والأريحية، الضبط الانفعالي والتحكم، المجازفة الإيجابية، الذكاء الوجداني، التوقعات الإيجابية والتفاؤل وأخيرا تقبل المسؤولية الشخصية، أما الفروق فقد توصلنا لوجود فروق ذات دلالة إحصائية في التفكير الإيجابي لصالح الإناث، وفي ضوء ما توصلنا إليه من نتائج قدمنا تفسيرات واقتراحات. The current study aimed at research into positive thinking among university students, University Amar Telidji lagouat and through snow the following questions:-what is the level of positive thinking among students? -What are the most common dimensions between undergraduate students? -Are there any statistically significant differences in the dimensions of positive thinking according to genre?, in order to answer these questions we used a measure of positive thinking to Abed elsattar (2010) on a sample of 200 students, where students numbered and came to the following results:-high level of positive thinking among university students, the most common dimensions according to the overall feeling of satisfaction first, then the positive acceptance of difference, love of learning and cognitive openness, tolerance and generosity, emotional and control exactly positive risk, emotional intelligence, positive expectations and optimism finally accepts personal responsibility, either The differences we have statistically significant differences in positive thinking for females. In the light of the results we have reached, we have provided explanations and suggestions.
مقال
Keywords: التفكير الإيجابي، الطلبة الجامعيين; positive thinking, university students